439 Primary symptoms in women with different histopathological subtypes of gynaecological sarcoma – results of a prospective intergroup registry for gynaecological sarcoma (REGSA – NOGGO RU1). (13th November 2020) - Roser, E; Pietzner, K; Brucker, S; Harter, P; Zocholl, D; Gimpel, A; Kalder, M; Bossart, M; Strauß, H; Wimberger, P; Armbrust, R; Marth, C; et al.
Abstract : Introduction: Gynaecological sarcomas are rare and there is very limited evidence about symptoms at primary diagnosis. Most knowledge is based on retrospective analysis. Methods: We present data of 410 patients (pts) in the primary situation. Overall, 87.91% of pts had documented symptom data, which were analysed descriptively. A distinction was made between pre- (prem., ≤52 yrs) and postmenopausal (postm., >52 yrs.). Results: The average age of pts was 56 yrs (range 15–88 yrs). Leiomyosarcoma (LMS) was diagnosed in 44.7%, endometrial stromal sarcoma (ESS) in 26.6% (62.6% low grade (LG-ESS) and 37.4% high grade (HG-ESS)). Undifferentiated sarcoma (US) and adenosarcoma (AS) were observed in 5.7% and 8.7% respectively. In prem. and postm. pts with LMS, the leading symptom (LS) was abdominal pain (ap) in 34.4%. and 39.5% respectively. In prem. HG-ESS the LS were ap and bleeding disorders (bd) in both 33.3%. In postm. HG-ESS and prem. LG-ESS the LS was vaginal bleeding (vb) in 29% and 33.3% respectively. In prem. AS the LS was ap in 27.3%, whereas in postm. AS it was postmenopausal bleeding (pb) in 29.2%. In prem. US the LS were bd and vb both at 66.7%. In postm. US the LS was ap in 47.4%. Conclusions: We analyzed the LS of different histopathological subtypes in primary gynaecological sarcoma for the first time. Bleeding disorders and abdominal pain are the main symptoms in all subtypes. Symptoms are heterogeneous and about every 5th woman reported unspecific symptoms. This underlines the importance of awareness for gynaecological sarcoma.